Narratives of domestic violence: policing, identity, and indexicality - Andrus, Jennifer (Cambridge University Press, 2024)
"This book is about narratives about interactions between police officers and domestic violence victim/survivors. Using theories of indexicality, identity, and narrative, I show how police officers conceive of victim/survivors and vice versa, as those(mis)conceptions are represented in narrative. I also analyze the ways in which identity emerges in and is performed via narrative constructions of domestic violence and encounters between police and victim/survivors. I argue that Identity emerges in an "indexical field" (Eckert) made up of different elements, each of which mean differently depending on the identity emerging in the field and the person telling the story. Thus, what domestic violence means and even what it looks like is different for victim/survivors than it is for police officers. Identity also emerges in storytelling when the storyteller constructs identities for characters in the story world that are then positioned against by the storyteller in the process of telling the story. Through the indexical and identity analysis of narrative, one issue that I address is the dismissal of emotional violence from the indexical field of domestic violence in police discourse. I argue that we need more resources to account for issues of emotional abuse in police responses to domestic violence"--